Beyond SmartNICs: Towards a Fully Programmable Cloud - Caulfield, Adrian; Costa, Paolo; Ghobadi, Manya (IEEE International Conference on High Performance Switching and Routing, 2018)
FPGA-based SmartNICs and programmable switches have been recently introduced to leverage hardware acceleration and custom pipelines inside the cloud infrastructure. These devices are capable of handling the per-packet processing needs at line rate, including load balancing, encapsulation, congestion management, and security. We argue, however, that the benefits provided by these new devices could extend beyond software-defined networking use cases and they prompt a shift towards a fully programmable cloud, which would enable hardware-software co-design across all layers, ranging from application to hardware and networks. In this paper, we focus on the potential of FPGA-based SmartNICs and programmable switches to realize this vision and illustrate some of the research challenges that need to be addressed to fully unleash its benefits.